Religion & politics : fit for polite company : a project of the John C. Danforth Center on Religion and Politics, Washington University in St.Louis - John C. Danforth Center on Religion and Politics (2017)
"[...] is an online news journal, dedicated to the two topics thought unfit for polite company. We feature articles from scholars and journalists who proceed from a single premise: that for better and for worse, religion and politics converge, clash, and shape public life. These intersections happen everywhere, from our homes to our courts, from the statehouse to the schoolhouse, in the lab and on the battlefield. We strive to publish a range of views, rather than promoting a specific political perspective. We honor frank and respectful debate. We inform these discussions by taking the long view, providing historical context, critical analysis, and thorough research with compelling writing"